Toward a multidimensional concept of organizational agility: a systematic literature review - Jawad Asghar; Dominik K. Kanbach; Sascha Kraus (Management Review Quarterly, 2025)
Organizational agility (OA), the ability of an organization to adapt to rapidly changing environments and reconfigure its structure and operations, has become a critical capability for achieving and sustaining competitive advantage. However, existing frameworks for OA often adopt narrow, industry-specific perspectives, neglecting the broader interplay of contextual factors, internal and external antecedents, and multidimensional capabilities. This study addresses this gap by conducting a systematic literature review (SLR) of 110 peer-reviewed articles from three leading academic databases. Guided by an inductive approach and the grounded theory methodology, this research identifies and categorizes the key antecedents of OA into four interconnected dimensions: contextual factors, fundamental attributes, vital enablers, and dynamic capabilities. The findings reconceptualize OA as a bundle of interrelated dynamic capabilities—encompassing macro-agility (e.g., strategic and partnering agility) and micro-agility (e.g., operational, innovation, and workforce agility)—rather than a singular construct. This multidimensional concept bridges theoretical gaps, integrating insights from contingency, agency and resource-based theories to explain the dynamic relationship between internal and external antecedents. The study offers a foundation for future research and provides actionable guidance for practitioners seeking to design agile organizations capable of thriving in dynamic capabilities.
Keywords: L20; M10; 650; Organizational agility; Dynamic capabilities; Systematic literature review